Peran Dukungan Keluarga sebagai Upaya Pengontrolan Hipertensi Pada Lansia : The Role of Family Support as an Effort to Control Hypertension in the Elderly Elderly - Afni Yan Syah; Neiliel Fitriana Anies (Fakultas Keperawatan Universitas Andalas, 2023)
As the elderly undergo physiological alterations during the aging process and are exposed to environmental influences that heighten their vulnerability to diseases, understanding the role of family support in mitigating health challenges, particularly hypertension, becomes paramount. Our research employed a correlational descriptive design with a cross-sectional approach to elucidate this relationship. Utilizing purposive sampling, we meticulously selected a cohort of 62 elderly individuals as our study participants. Data acquisition entailed the utilization of a comprehensive questionnaire comprising 25 statement items. Additionally, guided interviews, grounded in the questionnaire, were conducted. The rigorous statistical analysis was executed using the chi-square formula, applying a 95% confidence interval and an alpha (α) level of 0.05. The outcomes of this meticulous analysis yielded a compelling revelation—a statistically significant association between family support and the efficacy of hypertension control among the elderly (P value = 0.003, P value ≤ α). This empirical evidence underscores the pivotal role of family support in the management of hypertension among the elderly demographic. Consequently, we advocate for heightened attention and augmented support from families, underlining the importance of their involvement in the hypertension control efforts for the elderly. Such support can serve as a critical safeguard against the onset of complications stemming from hypertension within the elderly population. In summary, this study accentuates the significance of family support as a mitigating factor in the management of hypertension among the elderly, ultimately contributing to the avoidance of hypertension-related complications in this vulnerable demographic.